Influence of double calcination-milling route on the structural and microstructural properties of lead-free K0.5Na0.5NbO3 (KNN) ceramics. - Norni Hidayawati, Mat Daud; Dzetty Soraya, Abdul Aziz; Idza Riati, Ibrahim; Dayang Salyani, Abang Mahmod; Amir Azam, Khan; Nor Amalina, Ahmad (Penerbit UTM, 2023)
Potassium sodium niobate (KNN) has always beenone of the most potential candidates to replace lead-based piezoelectric ceramics due to its strong piezoelectric properties and environmentally friendly composition. A strong piezoelectric property is constantly influenced by the sample's densification as well as its microstructural characteristics. One of the current main issues with this KNN lead-free piezoelectric material is the difficulty in creating high-density samples by conventional preparation and sintering. Thus, KNN lead-free ceramics were synthesised using an improved solid-state method by introducing the double calcination-milling route to this process. The outcome demonstrates that, despite the presence of additional KNN secondary phases, the double calcination-milling approach contributed to the early creation of the KNN phase. When sintered pellets are subjectedto adouble calcination milling process, the XRD pattern revealed that the main peaks of the sample are indexed to orthorhombic K0.5Na0.5NbO3.The double calcination KNN pellet havea relative density of 90% densificationwhich is slightly higher than that of single calcination KNN pellet which shows 88% densification